Multi-omics investigation of interactions between persistent bacteria and Salmonella in the inflamed gut - Leleiwi, Ikaia, author; Wrighton, Kelly C., advisor; Prenni, Jessica, committee member; Szymanski, Erika, committee member; Weir, Tiffany, committee member (Colorado State University. Libraries, 2023)
Salmonella is a globally relevant enteric pathogen responsible for numerous outbreaks and debilitating illness yearly. Expansive tropism allows Salmonella to find bastion in zoonotic reservoirs including prominent food animals. Continued prophylactic antibiotic use in livestock and therapeutic antibiotic use in humans has increased selection for multi-drug resistant Salmonella varieties. Most of the current research on Salmonella enteric disease is performed absent complete native gut microbiota. Further, common murine models that could facilitate study of Salmonella in a robust community setting lack model-specific microbiome resources to accomplish the feat. Presented in this dissertation is a comprehensive catalogue of CBA/J mouse gut microbial genomes created as a resource for the research community. The genome database was used to recruit various omics data types to expand the current knowledge of Salmonella infection in a complex community setting, identifying community members robust to inflammation and with potential to further explore as probiotics. In Chapter 1, I review the current state of Salmonella pathogenesis in the context of the gut microbiome. The focus here is to survey the literature for prominent Salmonella mechanisms of infection and how they relate to both host and commensal microbes. I explore host responses to Salmonella and microbial metabolites capable of affecting Salmonella pathogenesis. This microbiome-centric take on Salmonella infection implies a need for comprehensive methods to examine microbes and their processes in vivo, including queries of genes and gene products. A special emphasis on multi-omics approaches is mentioned in this section as powerful tools to holistically study the complete Salmonella-included gut microbiome and to address deficiencies in prior work, ultimately providing more translatable results impacting human health. Chapter 2 outlines the creation of the CBAJ-DB – a first of its kind bacteria and virus genome collection produced from the gut communities of Salmonella infected and uninfected CBA/J mice. Relevance of this work to Salmonella research is explained, emphasizing the CBA/J model advantages to study enteric infection in unperturbed gut communities. Robust genome recovery from deep sequencing yielded over 2,000 bacterial metagenome-assembled genomes including novel bacteria strains and taxa with implications for other mouse breeds and human microbiomes. Viral genomes reconstructed from metagenomic sequencing were linked to bacteria hosts and mined for genes germane to bacteria function. The complete functional potential of the CBA/J gut community in infected and uninfected mice was also explored, detailing a decrease in immune-modulatory functional potential following Salmonella infection, and implying a potentially important role of Alistipes sp. in butyrate production. Importantly, work from this chapter provides the infrastructure for genome-resolved multi-omics investigations detailed in Chapter 3 that are critical to determine functional links between Salmonella and the commensal microbiota. In Chapter 3 additional metagenomic sequencing is combined with the CBAJ-DB and used to recruit metatranscriptomic and metabolomic data from infected and uninfected CBA/J mice. We reveal expression and metabolites that implicate numerous commensal bacteria with the flow of sulfur in the inflamed intestine, making it available for host oxidation to tetrathionate in support of Salmonella anaerobic respiration. Current dogma surrounding Salmonella lactate utilization from the host is also confronted by our data, which implies potential cross feeding on microbially derived D-lactate by Salmonella during peak infection. These expression data are supported by random forest and logistic regression modeling which determined genes for D-lactate production or utilization are important to Salmonella-association of other bacteria in the inflamed gut. Relatively abundant bacteria observed in Chapter 2 were confirmed to be active in infected communities and to be expressing genes relevant to Salmonella processes like chitinase, lactate dehydrogenase, and sulfatase. Not only does this chapter illustrate the utility of the CBAJ-DB but it highlights how multi-omics investigation in complete ecosystems can unveil results that may be different than claims made based on in vitro or reduced community in vivo studies. The final chapter presented here summarizes the key findings from Chapters 2 and 3 and offers avenues for future research including specific strain isolation from infected communities and subsequent Salmonella competition experiments to determine probiotic therapeutic potential. This dissertation aims to (1) Examine the diversity of the CBA/J mouse gut and provide a genomic resource to the microbiome community, (2) using various omics techniques, discover interactions between Salmonella and commensal bacteria that could impact pathogenesis, and (3) identify members of the inflamed community with probiotic potential that are indifferent to Salmonella or that display niche overlap for substrate competition with Salmonella. Ultimately, this dissertation provides a comprehensive examination of Salmonella infection amidst a whole and robust microbiome identifying important membership in the inflamed community and linking autochthonous processes with pathogenic ones to better understand Salmonella enteric disease.
Keywords: inflammation; multi-omics; CBA/J; Salmonella; microbiome